Eficacia de grupos fungicidas aplicados a dos frecuencias para el control de sigatoka negra (Pseudocercospora fijiensis) en banano - Mendoza Álvarez, Dayana Yonella (2022)
Black Sigatoka in banana cultivation is considered one of the most limiting diseases of production worldwide. The objective of this research was to evaluate the efficacy of fungicidal groups applied in two frequencies for the control of black Sigatoka (Pseudocercospora fijiensis) in bananas. The trial was carried out at the Experimental Farm La María of the State Technical University of Quevedo.